The formation of socialist personality in Leonov's novels of the 20-ies and 30-ies ("Sotj") - Kuzmenko, S. (Literatūra, 1974)
The main trend in the creative seeking of new ways in the prose of the twenties is the definition of social and moral potential of the new man born in the revolution. Leonid Leonov is of the opinion that the new moulding humanity must adopt together with the experiences of the contemporaneity also spiritual values amassed by the past in order to break on this basis the old world's resistance in all spheres of human existence, from external material conditions to the bottom of human soul. The problem of the enrichment of national character in the process of revolutionary ideas gaining strength in our society penetrates all the works of Leonid Leonov. This problem is successfully solved in his novel "Sotė". The character of Ivan Uvadjev, the main hero of the novel, undergoes a most complicated spiritual evolution.The complex of moral, ethic and aesthetic values which enters the notion of the new socialist humanity, is being strengthened, in the author's opinion, in this decisive moral reorientation.
Keywords: -